1994
DOI: 10.1002/ana.410350412
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of messenger RNA for peripheral myelin protein 22 in biopsied peripheral nerves of patients with Charcot‐Marie‐Tooth disease type 1A

Abstract: The human peripheral myelin protein 22 (PMP-22) gene has been mapped to chromosome 17p11.2 in the duplicated region associated with Charcot-Marie-Tooth disease type 1A. Southern blot analysis using PMP-22 as a probe indicated that the PMP-22 gene was duplicated in 5 patients from unrelated Japanese families with Charcot-Marie-Tooth disease type 1. In order to investigate whether or not an extra copy of PMP-22 has an effect on its gene expression, we analyzed relative expression of messenger RNA for PMP-22 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(47 citation statements)
references
References 29 publications
2
42
0
3
Order By: Relevance
“…These data, together with the evidence that the PMP22 gene is not disrupted within the tandem DNA duplication, support the hypothesis of a gene dosage mechanism as a cause of the pathogenesis of CMT 1A and HNPP. However, it has also been reported that the levels of PMP22 mRNA expression change with the progression of the disease (Hanemann et al, 1994;Yoshikawa et al, 1994). Thus the pathogenetic cascade of events seems to be more complex than initially anticipated.…”
Section: Introductionmentioning
confidence: 87%
“…These data, together with the evidence that the PMP22 gene is not disrupted within the tandem DNA duplication, support the hypothesis of a gene dosage mechanism as a cause of the pathogenesis of CMT 1A and HNPP. However, it has also been reported that the levels of PMP22 mRNA expression change with the progression of the disease (Hanemann et al, 1994;Yoshikawa et al, 1994). Thus the pathogenetic cascade of events seems to be more complex than initially anticipated.…”
Section: Introductionmentioning
confidence: 87%
“…In humans, a large proportion of patients with CMT and hereditary neuropathy with liability to pressure palsies are caused by altered PMP22 gene dosage resulting from a duplication or deletion, respectively, of a submicroscopic portion of chromosome 17 containing the human PMP22 gene (see Suter and Snipes, 1995a). Although controversial, the altered PMP22 gene dosage in CMT1A appears to be reflected by increased levels of PMP22 mRNA in Schwann cells (Yoshikawa, 1994) and PMP22 protein in peripheral myelin (Vallat, 1996; see also Hanemann, 1994). In mouse models alone, altered dosage of normal myelin genes causing myelination defects has now been described for the major compact myelin proteins in both the CNS and PNS, namely for MBP (Shine et al, 1992), P0 (Giese et al, 1992;Martini et al, 1995), PLP (Nave, 1994), and PMP22 (Adlkofer et al, 1996;Magyar et al, 1996;Sereda et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermyelination in CMT1A may be explained by elevated messenger RNA 42 and PMP22 protein expression; Vallat et al 39 were able to show a twofold increase in PMP22 protein expression in sural nerve biopsies of 2 CMT1A patients applying ultrastructural immunocytochemical quantitative analysis. Gabreëls-Festen et al 8 suggest that the myelin sheath gradually becomes too thick for the axon and consequently demyelination occurs.…”
mentioning
confidence: 97%